2023
DOI: 10.3233/cbm-220469
|View full text |Cite
|
Sign up to set email alerts
|

Hsa-miR-301a-3p inhibited the killing effect of natural killer cells on non-small cell lung cancer cells by regulating RUNX3

Abstract: BACKGROUND: Non-small cell lung cancer (NSCLC) is the most commonly diagnosed solid tumor. Natural killer (NK) cell-based immunotherapy is a promising anti-tumor strategy in various cancers including NSCLC. OBJECTIVE: We aimed to investigate the specific mechanisms that regulate the killing effect of NK cells to NSCLC cells. METHODS: Reverse transcription-quantitative PCR (RT-qPCR) assay was applied to measure the levels of hsa-microRNA (miR)-301a-3p and Runt-related transcription factor 3 (RUNX3). Enzyme-link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
0
0
Order By: Relevance
“…Consistent with previous research on NSCLC, the overexpression of hsa-miR-301a-3p can reduce the cytotoxicity of NK cells and decrease the secretion of IFN-γ and TNF by targeting Runt-related transcription factor 3 (RUNX3). This mechanism has also been shown to promote tumor progression in in vivo models ( Zhang et al, 2023 ). A study conducted by Gao et al also found decreased expression of miR-30c in primary NK cells from lung cancer patients compared to healthy controls.…”
Section: Innate Immunitymentioning
confidence: 99%
“…Consistent with previous research on NSCLC, the overexpression of hsa-miR-301a-3p can reduce the cytotoxicity of NK cells and decrease the secretion of IFN-γ and TNF by targeting Runt-related transcription factor 3 (RUNX3). This mechanism has also been shown to promote tumor progression in in vivo models ( Zhang et al, 2023 ). A study conducted by Gao et al also found decreased expression of miR-30c in primary NK cells from lung cancer patients compared to healthy controls.…”
Section: Innate Immunitymentioning
confidence: 99%